Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10995-016-1947-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Gestational Weight Gain: A Population-Based Cohort Study in Norway

Abstract: Objectives To explore ethnic differences in gestational weight gain (GWG). Methods This was a population-based cohort study conducted in primary care child health clinics in Groruddalen, Oslo, Norway. Participants were healthy pregnant women (n = 632) categorised to six ethnic groups (43 % were Western European women, the reference group). Body weight was measured at 15 and 28 weeks' gestation on average. Data on pre-pregnancy weight and total GWG until delivery were self-reported. The main method of analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 172 publications
(224 reference statements)
0
14
0
1
Order By: Relevance
“…Numerous studies explored more diverse racial/ethnic groups (Neser, 1963; Allen et al., 1994; Frisbie, Forbes & Hummer, 1998; Larouche et al., 2010; Bogaerts et al., 2012; Kowal, Kuk & Tamim, 2012; Gaillard et al., 2013; Hernandez-Rivas et al., 2013; Sommer et al., 2014; Bahadoer et al., 2015; Deputy et al., 2015; Kinnunen et al., 2016) but there were too few similarities within the data to compare GWG patterns. These studies are included in the summaries presented in Table 2 (2009 IOM guidelines).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies explored more diverse racial/ethnic groups (Neser, 1963; Allen et al., 1994; Frisbie, Forbes & Hummer, 1998; Larouche et al., 2010; Bogaerts et al., 2012; Kowal, Kuk & Tamim, 2012; Gaillard et al., 2013; Hernandez-Rivas et al., 2013; Sommer et al., 2014; Bahadoer et al., 2015; Deputy et al., 2015; Kinnunen et al., 2016) but there were too few similarities within the data to compare GWG patterns. These studies are included in the summaries presented in Table 2 (2009 IOM guidelines).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few and relatively small studies have examined associations of birth regions/countries with excessive GWG within a European context, e.g. [ 25 , 27 29 ]. Previous studies have indicated that women with non-European [ 28 ] and Moroccan [ 25 , 27 ] origin may have lower risk for excessive GWG than non-migrant women, whereas Kinnunen et al [ 29 ] did not identify any statistically significant differences across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 27 29 ]. Previous studies have indicated that women with non-European [ 28 ] and Moroccan [ 25 , 27 ] origin may have lower risk for excessive GWG than non-migrant women, whereas Kinnunen et al [ 29 ] did not identify any statistically significant differences across ethnic groups. Our findings show large variation in the odds of excessive GWG across birth regions although women born in Sweden had greater odds of excessive GWG than first-generation migrant women from some, but not all continents (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Parity was not associated with the prevalence of overweight among 35-74 year-old Turkish and Moroccan migrants living in the Netherlands 17 . In Norway, women of Eastern European and Middle Eastern origin gained more weight during pregnancy 19 and women of South Asian, Middle Eastern and African origin retained more weight postpartum 20…”
Section: Introductionmentioning
confidence: 99%